Faktor Predisposisi Rendahnya Penggunaan Kontrasepsi Intra Uterine Device (IUD) di Wilayah Kerja Puskesmas Gardujaya Tahun 2022 - Siti Rohmah; Silpia Aprilia; Sri Heryani; Siti Fatimah (Jurnal Obstretika Scientia, 2022)
In Indonesia the use of IUD contraceptives and others is 1.11%, Active Participants (PA) or the contraceptive prevalence rate (CPR) in West Java reaches 73.74%. In Ciamis Regency, the results of the Gardujaya Health Center were ranked as the second last to have the lowest IUD contraceptive achievement with a cumulative achievement of only 5 acceptors (0.3%) while the data for 2020 is the target number of 1128 people with the use of IUD KB as many as 11 people (0.97%). ) decreased IUD use by (0.4%). The purpose of this study was to describe the predisposing factors for the low use of Intra Uterine Device (IUD) contraceptives in the Gardujaya Health Center Work Area in 2022. This research method uses descriptive research. Samples in this study were 100 people. The sampling technique was randomly assigned to women of childbearing age who met the inclusion and exclusion criteria.Research results: This study found that most of the respondents had sufficient knowledge of 50 people (50%). Most of the respondents did not get husband's support as many as 58 people (58%). Most of the rsespondents have income that does not match the minimum wage as many as 62 people (62%).Conclusion: Most of the respondents have sufficient knowledge and Most of the respondents do not get husband's support, Most of the respondents have less income.It is hoped that the community can increase their knowledge or take part in counseling about family planning to make government programs successful through family planning programs.